Philosophy of Virtues. The Way to Wisdom in Aristotle and Primo Levi - Piredda, Patrizia (Politeia - História e Sociedade, 2021)
In this article, I aim to investigate the relationship between Aristotle’s ethics and Levi’s idea of ethics based on practical virtues. Understanding the former, in fact, permits us to better comprehend the philosophical undergrowth of the latter. And above all, it permits us to better understand how Levi, who constantly dealt with the ethical and aesthetic difficulty of narrating experience from an empiric and anti-idealistic point of view, used philosophy of virtues and wisdom as hermeneutic keys to understanding life.